Pengaruh Penambahan Tepung Mocaf Terhadap Sifat Organoleptik Dan Kadar Air Bakso Jamur Tiram (Muram) - Nur Hajriatun; Reni Sofiyatin; Iketut Swirya Jaya; Igde Narda Widiada (Jurnal Gizi Prima (Prime Nutrition Journal), 2017)
Background. Meatballs is one of processed livestock products are nutritious and much-loved community . Meatballs processed products in general use raw materials meat and flour . Alternative sources of vegetable protein which is now likely to be developed in the making meatballs are oyster mushrooms , in addition to protein-rich oyster mushrooms are also rich in fiber with binder mocaf flour. Research Methods. Experimental methods in the laboratory with a completely randomized design (CRD) of the factors is the addition of flour mocaf with the addition of three treatments cedar mocaf flour 30 % , 35 % and 40 % . Each treatment was repeated 5 times . The parameters observed organoleptic properties (color , smell , taste and texture) and water content . Data were analyzed using ANOVA test and Duncan's Multiple Range Test Test. Research Result. Extra flour mocaf have a significant effect on the flavor and moisture content (α < 0.05) , whereas the parameters of the color , smell and texture no significant effect (α > 0.05) . The average value of preference level panelists in terms of color , smell and taste are categorized like there is on the treatment t1. Conclusion. Extra flour mocaf have a significant effect on the flavor and moisture content (α< 0.05), whereas the parameters of the color, smell and texture no significant effect (α> 0.05).